2005
DOI: 10.1016/j.jphotobiol.2004.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the distribution of light, optical properties, drug concentration, and tissue oxygenation in-vivo in human prostate during motexafin lutetium-mediated photodynamic therapy

Abstract: It is desirable to quantify the distribution of the light fluence rate, the optical properties, the drug concentration, and the tissue oxygenation for photodynamic therapy (PDT) of prostate cancer. We have developed an integrated system to determine these quantities before and after PDT treatment using motorized probes. The optical properties (absorption (micro(a)), transport scattering (micro(s'), and effective attenuation (micro(eff)) coefficients) of cancerous human prostate were measured in-vivo using inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
169
1
4

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 193 publications
(176 citation statements)
references
References 38 publications
2
169
1
4
Order By: Relevance
“…We have previously shown that the human prostate has an inhomogeneous light-opacity distribution in vivo, which calls into question some of these assumptions. 12,13 A number of optimization algorithms used in brachytherapy are of interest for prostate photodynamic therapy. The most common ones are simulated annealing algorithms [14][15][16] and genetic algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that the human prostate has an inhomogeneous light-opacity distribution in vivo, which calls into question some of these assumptions. 12,13 A number of optimization algorithms used in brachytherapy are of interest for prostate photodynamic therapy. The most common ones are simulated annealing algorithms [14][15][16] and genetic algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 6(b) shows measured distribution of MLu drug concentration in prostate determined by absorption measurements at 732 nm, absorption spectroscopy measurements (see below) and fluorescence measurements [58]. The results of the three methods agree well for MLu drug concentration.…”
Section: Quantification Of Drug Concentration and Tissue Oxygenationmentioning
confidence: 58%
“…RUQ: right upper quadrant; LUQ: left upper quadrant; RLQ: left lower quadrant (taken from Ref. [58]). 3D reconstructed optical properties ((a) μ a and (b) ) at 732nm in human prostate before MLu-mediated PDT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations